Epilepsy in our lives - Schachter, Steven C. (Oxford University Press, 2008)
Gain insight as you read the stories of women living with epilepsy-- told in their own words. Women discuss the impact of epilepsy on their roles as mothers, wives, and individuals, and express their concerns about how epilepsy will affect pregnancy outcome, the health of their babies, and parenting. They share candidly how epilepsy impacts family planning, fertility and sexuality